Sisimpur’s reach and educational impact: Evidence from a national longitudinal survey of a Sesame Street project in Bangladesh. - Lee, H.J. (Sesame Workshop, 2009)

The role of government and NGOs in slum development: the case of Dhaka City - Habib, Enamul (Development in Practice, 2009)
This article addresses the situation of slums in Dhaka City in relation to government and NGO mechanisms and priorities for slum development and upgrading. It concludes with specific suggestions for better slum management in the Bangladesh capital.

Open and distance learning for basic education in South Asia: its potential for hard-to-reach children and children in conflict and disaster areas. - Morpeth, R; Creed, C; Cullen, J; Page, E; Raynor, J (United Nations Children's Fund, 2009)
Keywords: ___working_potential_duplicate